Mobilizing the Field Hospital: Pastoral Care as a Paradigm for Ministry with Young Adults - Jarzembowski, Paul (Religions, 2020)
When considering the Church and young adults, marketing or educational approaches are often used; however, these are inadequate to address the realities facing people in their 20s and 30s, including mental health, economic conditions, and racial and cultural injustice. What is needed is the development of a new ecclesial paradigm based on Pope Francis’s “field hospital” analogy, which emphasizes pastoral care as a primary step in ministerial accompaniment.